A Dictionary of South African English on Historical Principles: A Case of Lexical Invasion or Corpus Enhancement? - Hibbert, Liesel (Lexikos, 1997)
The DSAE (A Dictionary of South African English on Historical Principles) embraces linguistic diversity by including many Afrikaans lexemes and lexemes from African languages. In the advertising pamphlet the dictionary proposes to, among other things, improve communication, give access to education, change perceptions of SAfE (South African English) locally and internationally, improve historical and political perspectives and create a new South African identity. These statements are discussed in relation to popular local debates around "standards", language variation and policy. An overview is given of the current status of SAfE in the context of Southern Africa and Africa. Finally I argue in favour of the dictionary as documentary evidence of a living spoken language at a given point in history. Keywords: dictionary, lexicography, south african english, varieties of english, intercultural communication, multilingualism, south african identity, language planning, discourse communities, organization of african unity, colloquialisms, regionalisms, language shift, language change, dialect, loan-words, borrowings, africanisms, afrikaansisms, black south african english, linguistic charter for africa, standardization, corpus enhancement, lexical invasion, sociolinguistics